Different Early Responses of Laminariales to an Endophytic Infection Provide Insights About Kelp Host Specificity - Xing, Qikun; Bernard, Miriam; Rousvoal, Sylvie; Corre, Erwan; Markov, Gabriel V.; Peters, Akira F.; Leblanc, Catherine (Frontiers in Marine Science, 2021)
The filamentous algal endophyte Laminarionema elsbetiae is highly prevalent in European populations of the brown alga Saccharina latissima, but has also been found occasionally in the other kelp species Laminaria digitata. The presence of L. elsbetiae coincides with morphological changes in the hosts such as twisted stipes and deformed blades, however, little is known about the molecular bases of these algal host-endophyte interactions. Using a co-cultivation experiment, we showed that physiological and gene regulation responses, and later endophyte prevalences are different between the main and the occasional host. The contact with the endophyte L. elsbetiae induced a stronger and faster transcriptomic regulation in the occasional host L. digitata after 24 h, from which growth rate was later affected. During the first two days of co-cultivation, only 21 differentially expressed genes (DEGs) were common in both kelps, indicating a crucial difference between the molecular responses of the two hosts. By functional annotation, we identified DEGs related to host-endophyte recognition, defense response and cell wall modification. Our results suggest that expression pattern differences between the two kelps related to the recognition of the endophyte and later defense reactions could explain the variability of observed physiological responses and host-endophyte specificity in kelp natural populations.